Analisis aktivitas pembelajaran yang memfasilitasi keterampilan proses sains dasar pada buku tematik tema selalu berhemat energi kelas iv sekolah dasar - Atmojo, Idam Ragil Widianto; Saputri, Dwi Yuniasih; Wicaksana, Prinsa Damar (Jurnal Pendidikan Dasar, 2023)
This study was conducted to analyze learning activities that facilitate Basic Science Process Skills in students' thematic books. These skills include observing, classifying, inferring, measuring, predicting, and communicating skills. This study uses a qualitative approach. The data are in the form of student thematic books. The validity of the instrument used is the validity of the expert or Gregory and the data is validated by the theory of persistence and triangulation. Learning activities that facilitate communication appear a number of 92 items to be the most indicators. The second order is to display the data on the number of 47 items on the observing indicator. The third order with 27 items on the indicator concludes. Fourth order with 18 items on the grouping indicator. The last order with 17 items on measurement indicators and predictive indicators. There is one activity that is not facilitated by the Basic KPS in the student book, namely the manufacturing process activities obtained from the results contained in the conclusions. These considerations are based on the absence of activity content in students' thematic books. Thematic book for grade IV students, theme 2, contains sufficient and good Basic Science Process Skills.